Study of Rime in the Prose of Abi Al-Fadl Al-Mikali - Moustafa, Aisha Mohamad (Journal of Humanities & Social Sciences, 2021)
This research deals with the study of Rime in the prose of Abi Al-Fadl Al-Mikali, a study that dealt with this phenomenon in the fourth century AH. The Rime has an important impact on the literary text reaching its goal through mastering the selection of words and letters, considering their characteristics and sounds, so the recipient is delighted when he hears and the reader when he reads, and together it draws attention to the Rime in Abi Al-Fadl Al-Mikaly’s prose, that- this artistic color often leads On other inventive arts such as alliteration and iteration One of the most important recommendations that writers should not lose sight of in their writing is to stay away from the necessity of Riming in their artistic texts unless it is necessary, lest the literary work be spoiled by excessive embellishment and sophistication, so it loses its luster, and distorts its meaning. The recipient responds to the category work through its harmonious music and Rims that correspond to the requirements of the soul, and it is not possible in any way to isolate the rhythm of the Rime from the meaning and context, and the creator’s emotion. The ancient and contemporary critics were interested in this art and its impact on the artwork! Its place in prose is the place of weight in poetry, this art that entered the arts of literature, and gave it a sense of goodness, and a lot of interest in this art and commitment to it in the book of this century, except for what is rarely important.